Impact of land-use on tree and fruit morphometric variation of the bitter kola (Garcinia kola Heckel) in Benin: insight for domestication and production. - DADJO, Colombe; TOYI, Mireille; Nyende, Aggrey Bernard; SALAKO, Kolawolé Valère; ASSOGBADJO, ACHILLE EPHREM (My University, 2018)
Garcinia kola is an IUCN globally vulnerable species native in Benin where it is extinct in the wild. It is also one of the top ten priority non-timber forest products in Benin because of its socio-economic and medicinal values. Still, G. kola is neglected and underutilized. The morphological variation of G. kola traits was investigated in two land-use types (home gardens versus farmlands) where it is found in Benin with the goal of informing its domestication and production. A total of 79 trees identified in both land use types were characterized based on seventeen tree growth, leaves, fruit and seeds descriptors. Results found no significant difference between land-use types for tree height, first ramification height, crown height, crown diameter growth, blade width, petiole length, petiole diameter and number of seeds. However, stem diameter, blade length, fruit length, fruit width, husk weight, seed length, seed width and seed weight showed significant differences between land-use types. Eight (stem diameter, blade length, fruit length, fruit width, husk weight, seed length, seed width and seed weight) out of the initial descriptors were the most discriminant of trees according to land-use types. Values of most discriminant descriptors were low in home gardens and higher in farmlands. This study shows that land-use management can affect G. kola production, highlights the potential of domestication of the species, and suggests the need to fix morphological traits of fruits and nuts which are the most sought G. kola products.
Keywords: Benin; Clusiaceae; land-use management; morphological diversity; threatened species.